Revisão das espécies neotropicais de Xanthandrus Verral, 1901 (Diptera, Syrphidae) - Borges, Zuleica de Moraes (2001)
Presents results of taxonomic studies of Neotropical species of Xanthandrus Verral, 1901. The species belonging to this genus are easily distinguished from most of the other Syrphidae by their face with central prominence, metathoracic pleuron with fine pile ventrad of spiracle, and broad flat elliptic abdomen with markings. From the twelve species cited by THOMPSON et al., 1976, in the catalogue of the Diptera, six are redescribed: X bucephalus (Wiedemann, 1830); X cubanus Fluke, 1936; X mellinoides (Macquart, 1846); X mexicanus Curran, 1930; X nitidulus Fluke, 1937; and X plaumanni Fluke, 1937. Três espécies, X flavomaculatus Shannon, 1927, X palliatus (Fluke, 1945) and X simplex (Loew, 1861), are included in this dissertation, based in original descriptions, as no material was examined. Two species are synonymized, X biguttatus (= Argentinomyia longicornis (Walker, 1837)) and X quadrinotatus (Bigot, 1884) (= X bucephalus. X smithi (Smith, 1877) is cited in the catalogue as not found type, and without register in other museums. The type-material of X biguttatus, X cubanus, X mellinoides, X mexicanus, X nitidulus and X quadrinotatus was examined. Illustrations of the face, antennae, wing, male and female abdomen and terminalia, among other characters are presented, besides an identification key for the Neotropical species. The geographic register of the following species is enlarged: X bucephalus for Mexico, Bolivia and Brazil (Goiás, Mato Grosso, Rio de Janeiro and Rio Grande do Sul); X mellinoides for Brazil (Amazonas); X nitidulus for Brazil (Goiás, Mato Grosso, Rio de Janeiro, São Paulo and Paraná); X plaumanni for Colombia and Brazil (Minas Gerais).